Hillah Hukmi dalam Pengembangan (Legal Reform) Fatwa DSN MUI Tentang Pelaksanaan PPR Inden Syariah - Azhar Muttaqin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
This article discusses Hillah Hukmi in the context of developing the Fatwa of DSN-MUI regarding the implementation of the Sharia Inden PPR. The focus of the study is on analyzing indications of the use of hillah hukmi in the way the DSN-MUI stipulates a law. Especially in fatwa 101/DSN-MUI/X/2016 regarding the al-Ijaarah al-Maushuufah Fii al-Dzimmah contract or commonly abbreviated as IMFD. The research method used is qualitative by conducting content analysis which is commonly used in library research models with a normative juridical approach. This article finds that in the development of the fatwa of DSN-MUI in order to support the development of Islamic financial institutions, it is indicated to use the concept of hillah hukmi. This can be seen when the implementation of the Indent PPR Sharia is allowed using the Ijaarah al-Maushuufah Fii Dzimmah (IMFD) contract. DSN-MUI issued the fatwa because it was considered an alternative that could solve the problem of Indent PPR which was often hampered, and also became a complementary contract to the Musyaraakah Mutanaaqishah (MMQ) and Ijaarah Muntahiyah Bi Tamliik (IMBT) contracts. IMFD is indicated to contain hillah because the terms and substance of the contract are different. Namely, making the lease contract as the basis for allowing home ownership even though the essence of the contract is the sale and purchase of greetings. Qualitatively, this article reveals how the legal development carried out by the DSN-MUI in this way, especially in order to respond to public demands for the issuance of a fatwa that is able to accommodate the need for ownership of indent houses based on sharia principles.